Jung reader / edited by David Tacey - "Tacey, David (ed.)" (London, 2012)
Carl Gustav Jung was the pioneering founder of analytical psychology, a form of analysis that has revolutionised the approach to mental illness and the study of the mind. In this anthology, David Tacey brings together a selection of Jung's essays from his famous Collected Works.$1!# (BDivided into four parts, each with a brand new introduction, this book considers 17 of Jung$1 (Bs most important papers covering: the nature of the psyche archetypes religion and culture therapy and healing. This accessible collection is essential reading for undergraduates on analytical psychology courses, those on psychotherapy training courses, and students studying symbolism and dreams, or archetypal approaches to literature, cinema, religious studies, sociology or philosophy. The text is an informative introduction for general readers as well as analysts and academics who want to learn more about C. G. Jung's contribution to psychoanalysis, and how his ideas are still extremely relevant in the world today.s
Keywords: Jungian psychology